1989
DOI: 10.1002/food.19890331007
|View full text |Cite
|
Sign up to set email alerts
|

Role of zinc in regulating the testicular function. Part 1. Effect of dietary zinc deficiency on serum levels of gonadotropins, prolactin and testosterone in male albino rats

Abstract: Hypogonadism is a major manifestation of zinc deficiency in both humans and animals. In this study, we try to elucidate the main role of zinc in regulating the testicular function. Ninety male weanling albino rats were divided into three groups: control, zinc-deficient (ZD), and zinc-supplemented (ZS) groups. Six rats from each group were sacrificed every two weeks over a total period of ten weeks. Serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL) and testosterone (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
5
0
4
Order By: Relevance
“…In several studies, there was an increase in the secretion of gonadotrophins, presumably as a consequence of the loss of negative feedback to the hypothalamo-hypophyseal system (Lei et al, 1976;Root et al, 1979;Prasad, 1985). In the study by Hafiez et al (1989), however, the serum concentrations of gonadotrophins were not affected.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In several studies, there was an increase in the secretion of gonadotrophins, presumably as a consequence of the loss of negative feedback to the hypothalamo-hypophyseal system (Lei et al, 1976;Root et al, 1979;Prasad, 1985). In the study by Hafiez et al (1989), however, the serum concentrations of gonadotrophins were not affected.…”
Section: Introductionmentioning
confidence: 52%
“…In 1969, Underwood & Somers suggested that there may be two deficiency (5-17 pg Zn g~') where there are no clinical symptoms and body growth is normal, but testicular development and sperm production are markedly reduced. This contrast between the responses of the reproductive and other tissues suggests that 'mild' deficiency specifically affects the hormonal systems controlling testicular growth. A similar situ¬ ation has been suggested for the male rat and human, in which the effects of zinc deficiency appear to be expressed in the testis, specifically within the pathways controlling steroidogenesis, so that the secretion of androgens is reduced (McClain et al, 1984;Prasad, 1985;Hafiez et al, 1989). In several studies, there was an increase in the secretion of gonadotrophins, presumably as a consequence of the loss of negative feedback to the hypothalamo-hypophyseal system (Lei et al, 1976;Root et al, 1979;Prasad, 1985).…”
Section: Introductionmentioning
confidence: 90%
“…Zinc also induces the activity of 3␤-OH steroid dehydrogenase, which is the key enzyme used for testosterone biosynthesis [41]. Hafiez et al [42] also showed that zinc deficiency causes decreased levels of serum testosterone. In the present study an increase in testosterone and estradiol was observed after zinc supplementation.…”
Section: Discussionmentioning
confidence: 97%
“…Hpogonadismus kann bei männlichen Zn‐Mangelratten die Folge eine Mangels oder Verlustes bzw. einer verminderten Funktion an Leydig‐Zellen sein (L ei et al 1976; M ansour et al 1989). Möglicherweise ist es aber auch ein Sekundäreffekt, der durch die verminderte Futteraufnahme und dem damit verbundenen Energie‐ und Proteinmangel zu einer geringeren Wachstumsrate sowie einer allgemeinen Schwächung der Tiere führt.…”
Section: Diskussionunclassified